Role of Abdominal and Pelvic CT Scans in Diagnosis of Patients with Immunotherapy-Induced Colitis - Juan Ibarra Rovira; Selvi Thirumurthi; Melissa Taggart; Bulent Yilmaz; Heather Lin; Linda Lee Zhong; Chinenye Lynette Ejezie, MPH; Fechukwu O. Akhmedzhanov; Abdulrazzak Zarifa; Cheuk Hong Leung; David S. Hong; Raghunandan Vikram (Journal of Immunotherapy and Precision Oncology, 2022)
Introduction: Colitis is one of the most common immune-related adverse events in patients receiving immune checkpoint inhibitors. Although radiographic changes on computed tomography (CT), such as mild diffuse bowel thickening, mesenteric fat stranding, and mucosal enhancement, have been reported, the utility of CT in diagnosis of patients with suspected immune-related colitis is not well documented. The aim of this retrospective study was to determine the value of CT scans in diagnosis of immunotherapy-induced colitis. Methods: CT scans of the abdomen and pelvis of 34 patients receiving immunotherapy who had a clinical diagnosis of immunotherapy-induced colitis and 19 patients receiving immunotherapy without clinical symptoms of colitis (controls) were evaluated. Segments of the colon (rectum, sigmoid, descending, transverse, ascending, and cecum) were assessed independently by two abdominal imaging specialists, blinded to the clinical diagnosis. Each segment was assessed for radiographic signs such as mucosal enhancement, wall thickening, distension, and periserosal fat stranding. The presence of any of the signs was considered radiographic evidence of colitis. Results: CT findings suggestive of colitis was seen in 20 of 34 patients with symptoms of colitis and in 5 of 19 patients without symptoms of colitis. The sensitivity, specificity, positive predictive value, and negative predictive value for colitis on CT were 58.8%, 73.7%, 80%, and 50%, respectively. Conclusions: We found that CT had a low sensitivity, specificity, and negative predictive value for the diagnosis of immunotherapy-induced colitis. We therefore conclude that CT has a limited role in the diagnosis of patients with suspected uncomplicated immune-related colitis.